Modern Japanese aesthetics : a reader - Marra, Michael F. (University of Hawaiì Press, 1999)
Modern Japanese Aesthetics is the first work in English on the history of the Japanese philosophy of art, from its inception in the 1870s to the present. In addition to the historical information and discussion of aesthetic issues that appear in the introductions to each of the chapters, the book presents English translations of otherwise inaccessible major works on Japanese aesthetics, beginning with a complete and annotated translation of the first work in the field, Nishi Amane's Bimyogaku Setsu (The Theory of Aesthetics). In its four sections (The Subject of Aesthetics, Aesthetic Categories, Poetic Expression, Postmodernism and Aesthetics), Modern Japanese Aesthetics discusses the momentous efforts made by Japanese thinkers to master, assimilate, and transform Western philosophical systems to discuss their own literary and artistic heritage. Readers are introduced to debates between the unconditional supporters of Western ideas (Onishi Hajime) and more cautious approaches to the literary and artistic past (Okakura Kakuzo, Tsubouchi Shoyo). The institutionalization of aesthetics as an academic subject is discussed and the work of some of Japan's most distinguished professional aestheticians (Onishi Yoshimori, Imamichi Tomonobu), philosophers (Kusanagi Masao, Nishitani Keiji, Sakabe Megumi), and literary critics (Karatani Kojin) is included. Modern Japanese Aesthetics is a sophisticated and energetic volume on the process that led to the construction of aesthetic categories used by Japanese and, later, Western scholars in discussing Japanese literature and arts. This important work will be essential reading for anyone concerned with the formation of a critical vocabulary in Japan. Modern Japanese Aesthetics: A Reader is a companion volume to A History of Modern Japanese Aesthetics (UH Press, 2001).